已知函数f(x)=
(1)求证f(m)f(n)=-4; (2)当n-m取最小值时,点p(x1,y1),Q(x2,y2)(a<x1<x2<n),是函数f(x)图象上的两点,若存在x0使得f′(x0)=
|
(1)f′(x)=
,-4x2-2ax+4 (1+x2)2
依题意,m,n是方程-4x2-2ax+4=0的两根,
∴
,m+n=- a 2 mn=-1
f(m)f(n)=
•4m+a 1+m2 4n+a 1+n2
=16mn+4a(m+n)+a2 (mn)2+(m+n)2-2mn+1
=
=-4.-(16+a2)
+4a2 4
(2)∵n-m=(m+n)2-4x1x2
=
≥2,
+4a2 4
∴n-m取最小值时,a=0,n=1,m=-1,
∵f(x)在[-1,1]是增函数,0<x1<x2<1,
∴f′(x0)=
>0,从而x0∈(-1,1).f(x2)-f(x1) x2-x1
f′(x0)=
=4(1-x02) (1+x02)2
=f(x2)-f(x1) x2-x1
,4(1-x1x2) (1+x12)(1+x22)
即
=(1-x02) (1+x02)2
.1-x1x2 (1+x12)(1+x22)
∵(1+x12)(1+x22)=x12x22+x12+x22+1
>(x1x2)2+2x1x2+1
=(1+x1x2)2,
∴
=1-x02 (1+x02)2
<1-x1x2 (1+x12)(1+x22)
.1-x1x2 (1+x1x2)2
设g(x)=
,则g′(x)=1-x (1+x)2
,(x-1)2-2 (1+x)4
∴当x∈(0,1)时,有g′(x)<0,
∴g(x)是(0,1)上的减函数.
∴由g(x02)<g(x1x2),得x02>x1x2>x12,∴|x0|>x1.
由
=1-x02 (1+x02)2
,及0<1-x02<1-x1x2,1-x1x2 (1+x12)(1+x22)
得(1+x02)2<(1+x12)(1+x22)<(1+x22)2,
故1+x02<1+x22,即|x0|<x2,
∴x1<|x0|<x2.